Exploring Parental Experiences of Continuing Pregnancy in the Presence of a Life-Limiting Fetal Condition: A Qualitative Meta-Synthesis - Ouellette, Jodi (Université d'Ottawa / University of Ottawa, 2021)
Background: The field of perinatal palliative care aims to support the unique needs of parents who choose to continue pregnancy following the diagnosis of a life-limiting fetal condition (LLFC). As parents navigate this challenging trajectory, the support they receive from healthcare providers is crucial in shaping parental experiences. Objective: to critically reflect on existing literature and to reveal a deeper understanding of the experience of continuing pregnancy in the presence of a LLFC Design: Qualitative meta-synthesis Methods: The primary search strategy consisted of multiple searches within four electronic databases. The analysis was guided by thematic analysis. Results: This meta-synthesis included 29 qualitative studies. Three main themes were identified; time, uncertainty and relationships. These concepts exist concurrently within this trajectory and continuously influence each other as well as the overall experiences of parents. Conclusion: Nurses are encouraged to acknowledge the significance of the interconnectedness between these key concepts and to critically reflect on how their everyday interactions become part of parents’ lived experiences.
Keywords: Life-Limiting Fetal Condition; Perinatal Palliative Care